What if prescribed fire is not an option? A review of alternative treatments. - Michael G Andreu; Christopher Kinslow; Stephen Enloe (EDIS)
Fire has been a significant part of southeastern American forests for thousands of years. Prescribed fire is an effective method to achieve some land management goals, but sometimes it is not possible to use this tool. Fortunately, there are alternative treatment options that land managers can consider. Although none of these surrogate treatments will produce the same suite of benefits as prescribed fire, they can mimic some of the benefits that prescribed fire creates and are better than applying no treatments. This publication provides an overview for landowners and land managers that want to understand surrogate treatments and the economic and ecological tradeoffs associated with each treatment.